The Use of Audio Visual Media to Support the Role Playing Method: A Case Study of Theatre Learning in Cultural Arts Subjects - Hafiza, Rana; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe and analyze the use of audio-visual media as a supporter of the role-playing method in learning theatre arts in class IX SMPN 3 Lubuk Sikaping. The type of research is qualitative with a descriptive analysis method. The object of this research is the use of audiovisual media in the learning theater at SMPN 3 Lubuk Sikaping. Data collection was done through observation, interviews, and documentation. The data analysis was carried out with the steps of data collection, data reduction and categorization, data presentation, and conclusion drawing. The results showed that learning cultural arts, especially theatre material (musical drama) in Class IX at SMPN 3 Lubuk Sikaping, was presented using audio-visual media as a support for the role-playing method applied to students to achieve competence in learning. Learning went well; students were more excited and more focused with the media. On the other hand the role-playing method used in this learning was also very attractive to students' interest in learning theatre. hand, the use of audio-visual media as a supporter of the role-playing method in learning theatre arts in class IX at SMPN 3 Lubuk Sikaping is very influential in improving student learning outcomes and increasing student interest in honing the potential that exists in themselves.